Psychological Capital: Behavioral Insight for Study of Spirituality at the Workplace - جياد علي رزاق; دباس هاشم فوزي (Journal of Economics and Administrative Sciences, 2013)
Abstract This research aims to identify the role of Psychological Capital (PsyCap) in the Spirituality at the Workplace (SAW) for a sample of the teaching staff of the four Colleges of the University of Kufa reached (200) out of (470) teaching, and to achieve the objective of this research and through access to research and studies of foreign adopted researchers standards scales of research variables, since it relied on the model (Luthans, Youssef, et al., 2007) to represent the components of Psychological Capital (self-efficacy, and hope, and optimism, and resilience), and given the attention organizations in the human element because of its large role and direct the effectiveness of Organization, as well as that it is a source of sustainable competitive advantage of what is characterized by difficulty in tradition and complexity in the structure of social, necessary to pay attention to aspects of spirituality in the workplace and indulge them and harmonization between the values ​​of the person and his beliefs and his work, and a sense of originality and excellence; by relying on a scale (Kinjerski & Skrypnek, 2006) to measure the paragraphs of the spirituality at workplace (SAW), which consists of two variables (Engagement at work, and Spiritual Connection) as agreed upon by many of the studies, have used the questionnaire as a tool head for data collection, and hired a number of statistical tools to validate hypotheses such as mean and standard deviation and coefficient of simple correlation and the equation structure modeling, and analyzed by statistical programs (LISREL 8.54), (SPSS V.11.5) The results of research conform to most of the hypotheses formulated though conclusions at hand a set of recommendations of the most important of the concerned colleges The study sample components of psychological capital, because it encourages and promotes heavily on creating a work environment that takes care of the spiritual in the workplace.